Development of Popular Scientific Book on the Type of Shrimp in Coastal Waters of Tabanio for Enhancing Critical Thinking Skills of Senior High School Students - Yuliani Astuti; Muhammad Zaini; Aminuddin Prahatama Putra (Master Program of Biology Education, Universitas Lambung Mangkurat, 2021)
This development research is intended to describe the results of the development of a popular scientific book on shrimp species in the coastal waters of Tabanio, including validity, practicality, and effectiveness. The development design used was a design of Tessmer adaptation, including self-evaluation, expert testing, individual testing, and only up to small group tests. The object of research was a popular scientific book developed. Simultaneously, the research subjects consisted of 3 lecturers of Master Education of Biology, Lambung Mangkurat University, and five senior high school students of Abdul Kadir Panyipatan. Data were collected using the techniques of observation, questionnaires, and tests. The results showed that a popular scientific book was declared very valid based on expert validation results, while based on individual tests, the popular scientific book was declared very good. The popular science book that has been developed was considered practical because the results of student responses are 96.5% with very practical criteria. The result of the implementation of the popular science book was an average of 93.3%. The popular scientific book was declared effective because students' critical thinking skills increased in the Small Group, with 94.5% and N-Gain of 0.8 on high criteria. This popular scientific book has a systematic and structured writing flow. This book contains a discussion with high values of local potential. The design used is simple but easy to understand, and includes species identification, and displays original images taken directly from the coastal forest of Tabanio. All of these are the hallmarks of this popular science book.Abstrak Penelitian ini bertujuan untuk mendeskripsikan validitas, kepraktisan, dan keefektifan pengembangan buku ilmiah populer jenis udang di perairan pesisir Tabanio. Metode penelitian ini menggunakan model pengembangan Plomp dan Nieveen yang dibatasi pada tahap prototyping phase dimana evaluasi formatif berdasarkan Tessmer yang terdiri dari evaluasi diri, pendapat ahli, uji perorangan, dan hanya sampai uji kelompok kecil. Objek dalam penelitian ini ialah buku ilmiah populer yang dikembangkan, sedangkan subjek penelitian terdiri dari 3 dosen Magister Pendidikan Biologi ULM dan 5 siswa SMA Abdul Kadir Panyipatan. Teknik pengumpulan data dilakukan dengan observasi, angket dan tes. Hasil penelitian menunjukan buku ilmiah populer dinyatakan sangat valid berdasarkan hasil validasi ahli, sedangkan berdasarkan uji perorangan buku ilmiah populer ini dinyatakan sangat baik. Buku ilmiah populer yang telah dikembangkan dinyatakan praktis karena hasil respon siswa sebesar 96,5% dengan kriteria sangat praktis, dan hasil keterlaksanaan Buku ilmiah populer rata-rata 93,3%. Buku ilmiah populer dinyatakan efektif karena hasil kemampuan berpikir kritis siswa yang mengalami peningkatan pada Small Group dengan rata-rata 94,5% dan N-Gain sebesar 0,8 pada kriteria tinggi. Oleh karena itu, buku ilmiah populer “Jenis Udang di Perairan Pesisir Tabanio” ini dapat digunakan sebagai bahan pengayaan untuk melatihkan kemampuan berpikir kritis siswa SMA.